Heat Shock Protein 90 c-Terminal Inhibitors in Cancer Treatment - Yusuf Tutar (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2015)
Heat shock protein 90 (Hsp90) is 90 kDa highly conserved dimeric chaperone protein in prokaryotic and eukaryotic cells and it is localized in different parts of the cell. Hsp90AA1 (inducible) and Hsp90AB1 (constitutive) are available in the cytosol; Grp94 and TRAP1 exist in endoplasmic reticulum and mitochondria; respectively. In unstressed cells, expression level of Hsp90 corresponds to 1-2% of total cellular protein, and Hsp90 is responsible for protein folding, maintenance and degradation of misfolded proteins, cell cycle control, and cellular signaling. Hsp90 is composed of three domains: N terminal domain (NTD), middle domain (MD), and C terminal domain (CTD). Hsp90 needs ATP hydrolysis energy to perform chaperone functions. NTD has ATP binding sites and ATP hydrolysis leads to large conformational changes for interaction between substrate proteins and Hsp90. CTD contains a conserved EEVD motif and the dimerization interface to regulate ATPase process and binding of co-chaperones (i.e. Hop, CHIP) in protein folding process [1-3].